Differential Accounting Analysis in Decision Making or Buying Internet Vouchers on Haikal Tronik - Harahap, Puspita Wulandari; Isyanto, Puji; Septiawati, Rohma (International Journal Labs, 2023)
Business development in this digital era has encouraged many companies to innovate in order to maximize profits. This has driven management to make precise final decisions, one of which is using differential accounting analysis as a tool to analyze options between produce or purchase internet vouchers from Haikal Tronik. The purpose of this research is to examine the cost-effectiveness of Haikal Tronik's expenses using differential accounting analysis, particularly in decision-making between producing or purchasing products from an internet voucher supplier. The research method employed is quantitative descriptive. The data obtained include interview results, the company's general profile, direct documentation, and data related to costs incurred in relation to internet vouchers during Haikal Tronik's operations. These data were processed by classification and comparison between the alternatives of producing and purchasing. The research results from the differential accounting perspective show that if Haikal Tronik chooses to buy from the supplier, it will gain a profit of Rp 97,015,524. On the other hand, if it chooses to produce in-house, the resulting profit will be Rp 33,157,220. Therefore, purchasing is a more profitable option than producing internet vouchers.